2016
DOI: 10.3233/jpd-150680
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Submandibular Gland Synucleinopathy in Parkinson’s Disease, Dementia with Lewy Bodies and other Lewy Body Disorders

Abstract: BACKGROUND Clinical misdiagnosis, particularly at early disease stages, is a roadblock to finding new therapies for Lewy body disorders. Biopsy of a peripheral site might provide improved diagnostic accuracy. Previously, we reported, from both autopsy and needle biopsy, a high prevalence of submandibular gland synucleinopathy in Parkinson’s disease (PD). Here, we report on an extension of these studies to subjects with dementia with Lewy bodies (DLB) and other Lewy body disorders in 228 autopsied subjects from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 86 publications
1
46
2
1
Order By: Relevance
“…75 However, this group of researchers has not encountered a single case in which pathological a-syn was present in a peripheral body region but not in the CNS. 66 In contrast, Japanese studies have reported a number of cases with isolated a-syn pathology in the myenteric plexus of the esophagus and small intestine, the paraspinal sympathetic ganglia, adrenal glands, and also some cases with pathology restricted to the ganglia and thoracic IML. 30, [76][77][78] It should be noted that 1 of these studies was published prior to the era of a-syn immunohistochemistry, and the findings should be interpreted with caution.…”
Section: Pathological A-syn In Peripheral Organsmentioning
confidence: 95%
See 1 more Smart Citation
“…75 However, this group of researchers has not encountered a single case in which pathological a-syn was present in a peripheral body region but not in the CNS. 66 In contrast, Japanese studies have reported a number of cases with isolated a-syn pathology in the myenteric plexus of the esophagus and small intestine, the paraspinal sympathetic ganglia, adrenal glands, and also some cases with pathology restricted to the ganglia and thoracic IML. 30, [76][77][78] It should be noted that 1 of these studies was published prior to the era of a-syn immunohistochemistry, and the findings should be interpreted with caution.…”
Section: Pathological A-syn In Peripheral Organsmentioning
confidence: 95%
“…In diagnosed PD patients, pathological a-syn aggregations have been detected in various peripheral tissues, including the nervous plexuses of the gastrointestinal tract, [59][60][61][62][63] , heart, 64 salivary glands, 63,65,66 and skin. 67,68 However, to assess whether pathological a-syn appears during the preclinical phase, studies of prodromal cases, archived tissues, and autopsy material from neurologically intact individuals with or without incidental Lewy body disease (ILBD) are necessary.…”
Section: Pathological A-syn In Peripheral Organsmentioning
confidence: 99%
“…Post-mortem submandibular gland biopsies are positive for Lewy-type a-syn in patients with PD but not in healthy subjects [71], and this finding has made salivary a-syn one of the most investigated salivary biomarkers in neurodegeneration. Yet, both increases and decreases in salivary total a-syn have been reported [72][73][74].…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…Lewy body pathology has been reported to occur in early stages of PD in the submandibular gland and gut (Beach et al . ; Uchihara and Giasson ; Uchihara et al . ).…”
Section: Biomarkers For α‐Synuclein Pathologymentioning
confidence: 99%